Inotuzumab Ozogamicin as a Bridge to Stem Cell Transplantation in Relapsed Pediatric BCP‐ALL After Tisagenlecleucel: A Case Series - Margo Aertgeerts; Marleen Renard; Anne Uyttebroeck; Nancy Boeckx; Heidi Segers (Cancer Reports)
ABSTRACT Background CD19‐directed chimeric antigen receptor T‐cell therapy tisagenlecleucel has shown promising results in the treatment of pediatric patients with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL). However, around 50% of patients relapse after tisagenlecleucel. Following multiple relapses, limited treatment options are left, and the prognosis is dismal. We report on four pediatric patients who relapsed after tisagenlecleucel and were treated with inotuzumab ozogamicin (InO). Case Four patients with BCP‐ALL received tisagenlecleucel after second relapse (3/4) or refractory disease at first relapse (1/4). Three patients relapsed with CD19NEG/CD22POS BCP‐ALL, one with CD19POS/CD22POS BCP‐ALL. Following relapse, they received treatment with InO. After the first InO cycle, all achieved complete remission (CR), three without measurable residual disease. After two or three InO cycles, they underwent allogeneic hematopoietic stem cell transplantation (allo‐HSCT). One patient developed an isolated extramedullary relapse (IEM) in both anterior eye chambers six and nine months after allo‐HSCT and received palliative radiotherapy. This patient was in CR at the last follow‐up 25 months later. The other patients were also in CR at the last follow‐up (mean 31.3 months). Conclusion InO can be used successfully and safely for the treatment of CD22POS BCP‐ALL relapse after tisagenlecleucel as a bridge to allo‐HSCT in heavily pretreated pediatric patients.